Effect of Agrodyke Foliar Application on Growth and Yield of Two Varieties of Capsicum annuum: Foliar Application on Chili Growth and Yield - Mazli, Nurul Ain; Abd Manan, Fazilah; Sarobo, Zulaikha; Ridzuan, Raihana (Journal of Tropical Life Science, 2024)
Capsicum annuum is one of the most popular chili species cultivated and has become an important commodity crop in Malaysia. To overcome the shortage of Capsicum supply, foliar application can be utilized to increase chili yields. Foliar application requires only a minimal amount for effective use, rectifies nutrient deficiencies, and stimulates a rapid growth response. This research studied the effect of Agrodyke foliar fertilizer on the growth and yield of two varieties of C. annuum. Three treatments were applied to each chili variety, T0: control (no foliar application); T1: once a week (3 g/L) and T2: twice a week (3 g/L). The foliar application was initiated four weeks after germination. The results showed that Agrodyke foliar application at T2 resulted in the highest plant height (84.3 ± 3.9 cm) and stem diameter (1.3 ± 0.0 cm) for the Solok variety. For chlorophyll content, Agrodyke foliar application at T2 showed the highest levels in both Solok and Kulai varieties (67.3 ± 0.8 SPAD value and 67.4 ± 2.8 SPAD value, respectively). For individual fruit weight, Agrodyke foliar application at T2 in the Solok variety showed the highest weight (22.9 ± 2.1 g). In terms of fruit yield, Agrodyke foliar application at T1 in the Kulai variety produced the highest yield (123.3 ± 16.9 g). Furthermore, certain growth and yield attributes were positively correlated. Therefore, it can be concluded that Agrodyke foliar application at T2 provided better growth performance in terms of plant height and stem diameter for the Solok variety compared to the Kulai variety.